Signs and Symptoms Associated With Earlier Dialysis Initiation in Nursing Home Residents - Kurella Tamura, Manjula (2010)
BACKGROUND: Factors driving the trend of earlier dialysis initiation for persons with end-stage renal disease are unknown. We wished to determine the association of the number and type of signs and symptoms with timing of initiation of dialysis among US nursing home residents. STUDY DESIGN: Observational study SETTING AND PARTICIPANTS: We used data from the United States Renal Data System linked with the Minimum Data Set, a national registry of nursing home residents. The cohort consisted of 2402 nursing home residents who initiated dialysis between 1998 and 2000 and had at least two recorded clinical assessments in the year prior to dialysis initiation. PREDICTORS: We evaluated seven clinical signs and symptoms: dependence in activities of daily living, cognitive function, edema, dyspnea, nutritional problems, vomiting and body size. OUTCOMES: Earlier dialysis initiation was defined as an estimated glomerular filtration rate ≥15 ml/min/1.73m(2) at the start of dialysis. RESULTS: The median (25th percentile, 75th percentile) eGFR at the start of dialysis was 9.8 (7.4, 13.4) ml/min/1.73m(2) ([ND1]). After adjustment for age, sex, race and comorbid conditions, each additional sign or symptom was associated with a higher odds for earlier dialysis initiation (OR, 1.16 per symptom; 95% CI, 1.06-1.28), as was each adversely changing sign or symptom (OR, 1.26 per symptom; 95% CI, 1.16-1.38). The population attributable risk for earlier dialysis initiation associated with having one or more signs and symptoms of volume overload, cognitive decline, increasing activities of daily living dependence and weight loss was 31%; volume overload had the largest aggregate population attributable risk. LIMITATIONS: We lacked information about metabolic indications for dialysis initiation. CONCLUSIONS: Volume overload, cognitive decline, increasing activities of daily living dependence and weight loss were associated with earlier dialysis initiation; however, these factors explained less than one third of cases of earlier dialysis initiation in nursing home residents.